STUDY OF CATALYTIC Pd-Fe SYSTEM SUPPORTED ON CARBON HYDROGENATION CROTONALDEHYDE - Garrido S., Alfonso (2008)
It was prepared a bimetallic palladium–iron catalyst with support in carbon by the method of impregnation, following of drying and calcinations. The catalyst was characterized by DRX, Hydrogen DTP, TPR, BET and TEM. The test of the activity was made with the reaction of the hydrogenation of cronotaldehyde, obtained a selectivity to butanol of 23,65%.